Learning Medieval Astronomy through Tables: The Case of the Equatorie of the Planetis. (February 2016) - Falk, Seb
Abstract: Medieval tables can be rich sources of evidence about the practices of the mathematicians and astronomers who used them. This paper analyses an important set of tables, revealing their compiler's learning practices and elucidating a valuable document of inexpert science. Peterhouse, Cambridge MS 75.I, 'The Equatorie of the Planetis', is a late‐14th‐century compilation. It contains a treatise describing the construction and use of an equatorium (an astronomical instrument that computes the positions of the planets), bound with a collection of related astronomical tables. It was long thought to be written by the English poet Geoffrey Chaucer, but has recently been shown to be the work of a Benedictine monk, John Westwyk. This paper reassesses the manuscript as a monastic compilation. Westwyk copied a set of astronomical tables that suited his needs; their use supported and complemented the equatorium he describes in his treatise. He experimented with different techniques, cited astronomers whose work he admired (including Chaucer) and refined his tables in order to obtain the greatest possible precision. By reconstructing Westwyk's mathematical practices in compiling, computing and using tables that required and enabled a range of astronomical techniques, this paper paints a vivid picture of inexpert science in medieval Europe.